Cellulose-based functional hydrogels derived from bamboo for product design - Cao, Xiaobing; Li, Fei; Zheng, Tingting; Li, Guohui; Wang, Wenqian; Li, Yanjun; Chen, Siyu; Li, Xin; Lu, Yi (Frontiers in Plant Science, 2022)
Hydrogels have outstanding research and application prospects in the field of product design. Among them, the design and preparation of cellulose-based functional hydrogels derived from bamboo have attracted increasing research interest. Cellulose-based hydrogels not only have the skeleton function of hydrogels, but also retain excellent specificity, smart structural design, precise molecular recognition ability, and superior biocompatibility. Cellulose-based hydrogels show important application prospects in various fields such as environmental protection, biomedicine and energy. What’s more, they are potentially viable for application in food packaging and plant agriculture such as fertilizers release and crop production. Recently, researchers have extracted cellulose from bamboo and generated a variety of cellulose-based functional hydrogels with excellent properties by various cross-linking methods. In addition, a variety of multifunctional hybrid cellulose-based hydrogels have been constructed by introducing functional components or combining them with other functional materials, expanding the breadth and depth of their applications. Herein, we elaborate advances in the field of cellulose-based hydrogels and highlight their applications in food packaging and plant agriculture. Meanwhile, the existing problems and prospects are summarized. The review provides a reference for further development of cellulose-based hydrogels.